2017
DOI: 10.2298/fil1711599a
|View full text |Cite
|
Sign up to set email alerts
|

A characterization of the essential approximation pseudospectrum on a Banach space

Abstract: One impetus for writing this paper is the issue of approximation pseudospectrum introduced by M. P. H.Wolff in the journal of approximation theory (2001). The latter study motivates us to investigate the essential approximation pseudospectrum of closed, densely defined linear operators on a Banach space. We begin by defining it and then we focus on the characterization, the stability and some properties of these pseudospectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Note that if ε tends to 0, we recover the well-known definitions of essential spectra of T. In [18], M. P. H. Wolff has given a motivation to study the essential approximate pseudospectrum. In [3], the notion of the essential approximate pseudospectrum was extended by devoting the studies to the essential approximate spectrum. For ε > 0 and T ∈ C(X),…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that if ε tends to 0, we recover the well-known definitions of essential spectra of T. In [18], M. P. H. Wolff has given a motivation to study the essential approximate pseudospectrum. In [3], the notion of the essential approximate pseudospectrum was extended by devoting the studies to the essential approximate spectrum. For ε > 0 and T ∈ C(X),…”
Section: Introductionmentioning
confidence: 99%
“…♦[1] Let X be a Banach space, T ∈ C(X) and ε > 0. Then, λ σ e5,ε (T) if, and only if, for all D ∈ L(X) such that D < ε, we haveλ − T − D ∈ Φ(X) and i(λ − T − D) = 0.♦[3] Let T ∈ C(X) and ε > 0. The following properties are equivalent.…”
mentioning
confidence: 99%
“…In this paper, we interest by a generalization of eigenvalues called generalized trace pseudo-spectrum for an element in the matrix algebra to give more information about the matrix pencils of the form λV −U. For more information on various details on the above concepts, properties and applications of pseudo-spectrum [2,3,6,7,9], condition spectrum [1,4,5] and determinant spectrum [8]. Now, we introduce the new concept of the generalized trace pseudo-spectrum in the following definition.…”
Section: Introductionmentioning
confidence: 99%
“…For ε > 0, it can be shown that σ ε (T) is a larger set and is never empty. The pseudospectra of T are a family of strictly nested closed sets, which grow to fill the whole complex plane as ε → ∞ (see [3,8,18,19]). From these definitions, it follows that the pseudospectra associated with various ε are nested sets.…”
Section: Introductionmentioning
confidence: 99%